Impact of electronic and blended learning programs for manual perineal support on incidence of obstetric anal sphincter injuries: a prospective interventional study - Hadil Ali-Masri (BMC Medical Education, 2018)
Abstract Background Obstetric anal sphincter injuries (OASIS) are associated with anal incontinence, dyspareunia and perineal pain. Bimanual perineal support technique (bPST) prevents OASIS. The aim of this study was to assess the effect of two different bPST training-methods on OASIS incidence. Methods This is a prospective-interventional quality improvement study conducted in two Palestinian maternity units between June 1 2015 and December 31 2016. Women having spontaneous or operative vaginal-delivery at ≥24 gestational-weeks or a birthweight of ≥1000 g (n = 1694) were recruited and examined vaginally and rectally immediately after vaginal birth by a trained assessor. Data on baseline OASIS incidence were collected during Phase-1 of the study. Subsequently, birth attendants in both maternity units were trained in bPST using two training modalities. A self-directed electronic-learning (e-learning) using an animated video was launched in phase-2 followed by a blended learning method (the animated e-learning video+ structured face-to-face training) in phase-3. OASIS incidence was monitored during phases-2 and 3. Variations in OASIS incidence between the three phases were assessed using Pearson-χ2-test (or Fisher’s-Exact-test). The impact of each training-method on OASIS incidence was assessed using logistic-regression analysis. Results A total of 1694 women were included; 376 in phase-1, 626 in phase-2 and 692 in phase-3. Compared to Phase-1, OASIS incidence was reduced by 45% (12.2 to 6.7%, aOR: 0.56, CI; 0.35–0.91, p = 0.018) and 74% (12.2 to 3.2%, aOR, 0.29, CI; 0.17–0.50, p < 0.001) in phases-2 and 3, respectively. There was also a significant reduction in OASIS incidence by 52% from phase-2 to phase-3 (6.7% (42/626) to 3.2% (22/692), p = 0.003). These reductions reached statistical significance among parous-women only (aOR: 0.18, CI; 0.07–0.49, p = 0.001) after the first training method tested in phase-2. However, the reduction was significant among both primiparous (aOR: 0.39, CI; 0.21–0.74, p = 0.004) and parous-women (aOR: 0.11, CI; 0.04–0.32, p < 0.001) after implementing the blended learning method in phase-3. Conclusion The animated e-learning video had a positive impact on reducing OASIS incidence. However, this reduction was enhanced by the use of a blended learning program combining both e- learning and face-to-face training modalities. Study registration number ClinicalTrialo.gov identifier: NCT02427854, date: 28 April 2015.